Financial Hardship and Saving Behaviour: Bayesian Analysis of British Panel Data - Sarah Brown; Pulak Ghosh; Bhuvanesh Pareek; Karl Taylor (Institute of Labor Economics (IZA), 2017)
We explore whether a protective role for savings against future financial hardship exists using household level panel data. We jointly model the incidence and extent of financial problems, as well as the likelihood of having secured debt and the amount of monthly secured debt repayments, allowing for dynamics and interdependence in both of the two-part outcomes. A two-part process is important given the considerable inflation at zero when analysing financial problems. The model is estimated using a flexible Bayesian approach with correlated random effects and the findings suggest that: (i) saving on a regular basis mitigates both the likelihood of experiencing, as well as the number of, future financial problems; (ii) state dependence in financial problems exists; (iii) interdependence exists between financial problems and secured debt, specifically higher levels of mortgage debt are associated with an increased probability of experiencing financial hardship.
Keywords: C11; D12; D14; R20; 330; Bayesian modelling; financial hardship; saving; zero inflation